NovelSNPer: A Fast Tool for the Identification and Characterization of Novel SNPs and InDels. (2011) - Aßmus, Jens; Schmitt, Armin O.; Bortfeldt, Ralf H.; Brockmann, Gudrun A.
Abstract : Typically, next-generation resequencing projects produce large lists of variants. NovelSNPer is a software tool that permits fast and efficient processing of such output lists. In a first step, NovelSNPer determines if a variant represents a known variant or a previously unknown variant. In a second step, each variant is classified into one of 15 SNP classes or 19 InDel classes. Beside the classes used by Ensembl, we introduce POTENTIAL_START_GAINED and START_LOST as new functional classes and present a classification scheme for InDels. NovelSNPer is based upon the gene structure information stored in Ensembl. It processes two million SNPs in six hours. The tool can be used online or downloaded.